Implementation of Quality Management on Service Quality at PT PLN (Persero) UP3 Sumedang - Rimbani, Silvia Herawati; Dwinova, Ghea Aulia; Rohman, Nursaeful; Febrianika, Luthfianeu; Kartiwa, Aa (SINTESA, 2024)
This study explores the implementation of quality management in improving service quality at PT PLN (Persero) UP3 Sumedang, an operational unit of PT PLN (Persero) responsible for electricity services in the Sumedang and Majalengka regions. Using a qualitative method, this research analyzes the quality management practices applied, evaluates their impact on service quality, and provides recommendations for further improvement. The results show that focusing on customers, enhancing service quality, responsiveness to complaints, technology utilization, employee training, and a commitment to continuous improvement are key success factors in quality management implementation. Effective quality management at PT PLN (Persero) UP3 Sumedang can increase customer satisfaction and loyalty, reduce complaints, enhance the company's reputation, and optimize operations. This study is expected to provide guidance for other public service providers in their efforts to improve operational performance and service through quality management